Developing a fast cordless soldering iron via induction heating (2014)
This study aims to present the design of a new soldering iron for welding electronic components that work via AC magnetic fields. Moreover, the device has been designed to operate in cordless mode. The system comprises of a resonant inverter that is capable of generating an alternating magnetic field of 250 kHz in the center of a coil of 11 wires. The heating element is a cylindrical piece of ferromagnetic stainless steel with a concentric core of copper, which is maintained in contact with a standard and commercial tip. Additionally, we determined the power factor and the efficiency of the energy transfer with a maximum power consumption of 134 watts. The system represents a good tool suitable for the realization of development boards or electronic tasks.